2013
DOI: 10.31018/jans.v5i2.344
|View full text |Cite
|
Sign up to set email alerts
|

Study of health and nutritional status of the workers working in knitting industry located at Kanpur, India

Abstract: Knitting industry occupies a pivotal position in the economic dynamism of various countries. The workers in the knitting industry suffer from various types of health risk factors. The risk in the knitting industry is higher and the ability to control it is lower. The majority of the problems are due to poor work environment, manual work condition and long hours of static working posture in the knitting industry. The present study was conducted to study the health and nutritional status of the workers in knitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…A cross-sectional study conducted in Brazil among workers of different industries found that 19% of the male workers were obese and 42% were overweight which is almost double than our study [1]. Another study conducted in Kanpur India among workers working in the knitting industry revealed that 11% of the workers were overweight which is lower than our study and 10% were obese [27]. A study conducted among US workers showed that 27.7% of the workers met the BMI criteria of obesity which is higher than this study [28].…”
Section: Discussioncontrasting
confidence: 75%
“…A cross-sectional study conducted in Brazil among workers of different industries found that 19% of the male workers were obese and 42% were overweight which is almost double than our study [1]. Another study conducted in Kanpur India among workers working in the knitting industry revealed that 11% of the workers were overweight which is lower than our study and 10% were obese [27]. A study conducted among US workers showed that 27.7% of the workers met the BMI criteria of obesity which is higher than this study [28].…”
Section: Discussioncontrasting
confidence: 75%
“…They are inherently political, as well as technical [6]. These three issues entail choices that are taken by both national governments and international organisations as well as by individual nations [9].…”
Section: Introductionmentioning
confidence: 99%